Adolescents’ Perceptions Regarding Effective Tobacco Use Prevention Strategies for their Younger Counterparts: A Qualitative Study in Malaysia - Zin, Faridah Mohd (Asian Pac J Cancer Prev, 2016)
PURPOSE: The present qualitative study explored adolescents’ perceptions regarding effective strategies to prevent adolescents from using tobacco products (TP). Apart from the commercial TPs, there has been emerging use of alternatives such as vapes, e-cigarettes and shisha. This unfortunate phenomenon continues despite the currently available preventive strategies. Thus, understanding of the perceptions of the current generation would be valuable to provide new insights. METHODS: Purposive sampling was utilized to recruit 40 adolescents between the age of 15 and 16 years old attending public daily secondary schools. Eight focus group discussions were conducted among the TP users, ex-users and non-users. Data were analyzed using a thematic content analysis procedure with NVivo. RESULTS: Among barriers with the currently available strategies were having teachers who smoke tobacco, addiction to nicotine and self-perceptions of being healthy. The content of any program should include knowledge on negative outcomes of using tobacco products and awareness of the legislation together with ways to overcome peer and family influence including improving self-efficacy and refusal skills. Strategies were suggested to be delivered using information technology which provides interactive learning and visual effects. CONCLUSIONS: Adolescents agreed that the content and delivery of tobacco use prevention strategies need to be revised to suit the current generation to ensure sustainability.